The Persistent Health Burden: Understanding Black South African Working-Class Men’s Experiences of Living with Tuberculosis - Madhuha, Edmond (University of the Witwatersrand, Johannesburg, 2024)
This study is the culmination of ethnographic fieldwork on black working-class men’s tuberculosis (TB) illness experiences, conducted during 2020 and 2021 in Modimolle Township, a non-mining, peri-urban community of South Africa’s Limpopo province. The study examines ways men construct masculine identities and how this provides a lens through which to understand their health-seeking behaviours when beset with TB suggestive symptoms. Men’s construction of masculine identities further helps shed light on their tuberculosis illness experiences and treatment outcomes. Tuberculosis scholarship in South Africa has justifiably focused on the impact of silicosis on men, and the subsequent oscillating labour migration as pathways through which the disease is contracted and transmitted to non-mining communities of the country and the southern African region. Men’s experiences with tuberculosis disease in non-mining communities have however received little attention in South Africa’s extensive tuberculosis research. Drawing from the African-centred theories of masculinity is a conceptualisation of men that I call masculinity in sociability. This thesis of masculinity in sociability manifests when men gather in spaces and engage in social behaviours and practices such as sharing cigarettes and beer within proximity of each other. I demonstrate that masculinity in sociability is informed by the socio-cultural values of seriti (dignity, integrity, and respect), maitshwaro (manners and conduct), and botho (humanness, ubuntu, the sum of human values), which engender a sense of belonging and community among men in specific masculinised spaces. I argue that masculinity in sociability illuminates the crucial and intricate interplay between masculinised, enclosed physical spaces and shared air as possible ways tuberculosis is contracted and transmitted among men. Considering that masculinity in practices of sociability is predominantly performed in masculinised spaces, I further argue that its manifestation concomitantly recedes when men experience TB illness in the private sphere of the home. The thesis demonstrates that men’s exposure, infection, diagnosis, and response to tuberculosis treatment are influenced by their masculinity. In contrast to the public performances of masculinity for the purposes of sociability, the vulnerabilities brought about by tuberculosis create a significant disruption in individuals’ life stories. This disruption is evident in men’s experiences of losing their sources of income and becoming dependent on the care provided by mothers and spouses, which can be experienced by men as a return to a more childlike state. From health through to the continuum of TB diagnosis and illness experience, the thesis shows that masculinity exhibits a remarkable flexibility and adaptability. The thesis contributes to our understanding of masculinities by offering a condensed perspective on how iv economically marginalised black men perceive and undergo the challenges of tuberculosis. Using metaphors, men depict TB as a debilitating and insidious illness condition which unmasks their vulnerability.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Modimolle; tuberculosis; African centred theories of masculinity; masculinity in sociability; illness experiences; SDG-8: Decent work and economic growth; SDG-10: Reduced inequalities